PRC1 coordinates timing of sexual differentiation of female primordial germ cells - Yokobayashi, Shihori; Liang, Ching-Yeu; Kohler, Hubertus; Nestorov, Peter; Liu, Zichuan; Vidal, Miguel; van Lohuizen, Maarten; Roloff, Tim C.; Peters, Antoine H. F. M. (Nature (London), 2013)
The Polycomb repressive complex 1 (PRC1) is found to have important gene-dosage-dependent and sex-specific roles in primordial germ cell (PGC) development, including the maintenance of high levels of Oct4 and Nanog and ensuring the proper timing of meiosis through the suppression of retinoic acid signalling in female PGCs. PRC1 role in germ cell development Polycomb group proteins are involved in the transcriptional repression of developmental regulators in embryonic stem cells, where they maintain pluripotency and cell identity during subsequent development. Antoine Peters and colleagues have studied the function of the Polycomb repressive complex 1 (PRC1) in the development of mouse primordial germ cells (PGCs). They observed multiple sex-specific roles of PRC1 in development. PRC1 is required for the maintenance of high levels of expression of the transcription factors Oct4 and Nanog. And by suppressing retinoic acid signalling provided by the somatic compartment of the female genital ridge, PRC1 also ensures proper timing of meiotic induction. In mammals, sex differentiation of primordial germ cells (PGCs) is determined by extrinsic cues from the environment 1 . In mouse female PGCs, expression of stimulated by retinoic acid gene 8 ( Stra8 ) and meiosis are induced in response to retinoic acid provided from the mesonephroi 2 , 3 , 4 , 5 . Given the widespread role of retinoic acid signalling during development 6 , 7 , the molecular mechanisms that enable PGCs to express Stra8 and enter meiosis in a timely manner are unknown 2 , 8 . Here we identify gene-dosage-dependent roles in PGC development for Ring1 and Rnf2 , two central components of the Polycomb repressive complex 1 (PRC1) 9 , 10 . Both paralogues are essential for PGC development between days 10.5 and 11.5 of gestation. Rnf2 is subsequently required in female PGCs to maintain high levels of Oct4 (also known as Pou5f1 ) and Nanog expression 11 , and to prevent premature induction of meiotic gene expression and entry into meiotic prophase. Chemical inhibition of retinoic acid signalling partially suppresses precocious Oct4 downregulation and Stra8 activation in Rnf2 -deficient female PGCs. Chromatin immunoprecipitation analyses show that Stra8 is a direct target of PRC1 and PRC2 in PGCs. These data demonstrate the importance of PRC1 gene dosage in PGC development and in coordinating the timing of sex differentiation of female PGCs by antagonizing extrinsic retinoic acid signalling.